Air evacuation during vacuum bag only prepreg processing of honeycomb sandwich structures: In-plane air extraction prior to cure. (January 2015) - Levy, Arthur; Kratz, James; Hubert, Pascal
Abstract: Out-of-autoclave (OoA) prepregs offer good in-plane air permeability that enable efficient in-plane air-extraction. In this paper, OoA prepregs skins were applied to honeycomb sandwich structures, to act as in-plane air extraction media during the vacuum hold prior to cure. An in-plane extraction model was developed to predict the pressure drop in a honeycomb sandwich structure. The model was experimentally validated by measuring the local pressure in a 1 m long sandwich structure. The model provides design guidelines vacuum hold duration to achieve a given final pressure in the part prior to cure. Finally, the in-plane and transverse extraction strategies were compared for large parts. The in-plane extraction was faster for parts smaller than 0.4 m .